The possibility of using the target costing technique to achieve competitive advantage-an applied study in the men’s clothing factory in Najaf. - حسين جميل غافل (Iraqi Journal for Administrative Sciences, 2024)
The aim of this study is to demonstrate the extent to which the targeting- cost technology can be used in industrial companies as one of the important techniques used by companies in determining the target sales price of the product in the competition market after considering the customer’s requirements, desires, by reaching target cost appropriate quality of the product, then reaching the target cost. The study shows that traditional accounting systems which is not Determine the sales price first, but rather that determine the cost plus appropriate profit margin. Target costing determining the market price first, then target profit margin, also the difference between the market price the target profit representing Target Cost. The directors of companies and industrial Plants in cooperation with universities, to form a dialogue panel in front of technological developments, administrative and accounting to be able to confront any developments in the Indus trial Field and to keep by adopting the latest developments in cost there fore these companies to achieve more profits in the prevailing competitive environment.